Microbial contamination of domiciliary nebulisers and clinical implications in chronic obstructive pulmonary disease. Issue 1 (28th February 2014) - Jarvis, S; Ind, P W; Thomas, C; Goonesekera, S; Haffenden, R; Abdolrasouli, A; Fiorentino, F; Shiner, R J
Abstract : Background and purpose: Domiciliary nebulisers are widely used in chronic obstructive pulmonary disease (COPD) but nebuliser cleaning practice has not been assessed in patients with COPD who are often elderly and may have severe disease and multiple comorbidities. We aimed to evaluate microbial contamination of home nebulisers used by patients with COPD. Methods: Random microbiological assessment of domiciliary nebulisers was undertaken together with an enquiry into cleaning practices. We also examined the effectiveness of the trust-wide cleaning instructions in eradicating isolated microorganisms in a laboratory setting. Results: The mean age of patients in this study was 71 (range 40–93) years, and in 68% of patients a large number of significant comorbidities were present. Forty-four nebuliser sets were obtained and 73% were contaminated with microorganisms at >100 colony forming units/plate. Potentially pathogenic bacteria colonised 13 of the 44 nebulisers (30%) and organisms isolated included Pseudomonas aeroginosa, Staphylococcus aureus, multidrug resistant Serratia marcesans, Escherichia coli and multiresistant Klebsiella spp, Enterobacteriaceae and fungus Fusarium oxysporum. Washing of nebuliser masks, chambers and mouthpieces achieved complete eradication of Gram-positive bacterial and fungal flora. Gram-negative organisms were incompletely eradicated, which may be attributed to the presence of biofilms. We also found that in patients with pathogenic organisms cultured on the nebuliser sets, there was a higher probability of occurrence of a COPD exacerbation with a mean number of exacerbations of 3.3 (SD=1) per year in the group in whom pathogens were isolated compared with 1.7 (SD=1.2) exacerbations per year in those whose sets grew non-pathogenic flora (p=0.02). Conclusions: Nebulisers contaminated with microorganisms are potential reservoirs delivering serious pathogens to the lung. Relationships between nebuliser contamination, clinical infection and exacerbations require further examination, but is a potential concern in elderly patients with COPD with comorbidities who fail to effectively maintain reasonable standards of nebuliser cleanliness.